A novel local impedance algorithm and contact force sensing to guide high power short duration radiofrequency ablation is efficient and safe for circumferential pulmonary vein isolation. (24th May 2021) - Schreieck, J; Heinzmann, D; Scheckenbach, C; Gawaz, M; Duckheim, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Local impedance (LI) drop can predict sufficient lesion formation during radiofrequency ablation (RF). Recently, a novel ablation catheter technology able to measure LI and contact force has been made available for clinical use. High power short duration (HPSD) RF ablation has been shown to be feasible for atrial fibrillation (AF) ablation with short procedure time. We used LI drop and plateau formation to guide duration of 50 Watt RF power applications for circumferential pulmonary vein isolation (PVI). Methods: Consecutive patients with indication for de novo AF ablation (n = 32, age 65 ± 10 years) with paroxysmal (n = 16) or persistent (n = 16) AF underwent ultra high density 3D mapping of the left atrium and catheter ablation. Thereafter, ipsilateral PV encircling with 50 Watt RF-applications targeting an interlesion distance of ≤ 6mm and a contact force of 10-30g was performed. Duration of HPSD RF application between 7-15s was guided by impedance drop >20 Ohm and plateau formation of LI. Further ablation strategy was left to the investigator's discretion. Esophageal temperature measurement was performed using a three thermistor catheter with temperature cut off 39.0°C. In case of temperature rise or very near esophageal contact to the circumferential line, RF application time was shortened to 7s. Patients underwent adenosine testing after PVI. Previously we performed all types of AF ablation using an LI guided HPSD ablation without contact force measurement capability in 80 patients. Results: Complete PVI was achieved in all pts with only 13.5 ± 4.3 min cumulative RF application duration and an ablation procedure duration of 46.5 ± 10.4 min with the novel LI measuring catheter. First-pass isolation of ipsilateral veins was achieved in 75% of circles. Recurrence of PV conduction during waiting period (20min) and adenosine testing occured in 25% of circles, and was reablated in most patients with a single spot of HPSD application. Using 94 ± 36 RF application per patient, mean maximum LI drop was 23.6 ± 4.0 Ohm. Reconnected fibers were associated with low LI drop due to instability of contact in most cases due to breathing in case of difficult sedation of the patients. No serious complications occurred in all 32 pts using HPSD with the novel contact force catheter design. Conclusion: Guiding of HPSD RF ablation by LI is highly efficient and safe. A novel local impedance algorithm in combination with contact force sensing enable short PVI times with low early recurrence of PV conduction. Prediction of permanent lesions seems possible and the only limitation seems to be unstable RF catheter contact due patients breathing. Follow up have to be waited.